SUBSTITUSI TEMPE TERHADAP TEPUNG TERIGU PADA KARAKTERISTIK KUE CUBIT - Dewa_Ayu Oka Wahyuni; Badrut Tamam; Anak Agung Nanak Antarini (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2021)
Tempe is a traditional Indonesian food made from soybeans that has undergone a fermentation process. Cubit cakes have a small size (about 4 cm in diameter). In making cubit cakes using a mixture of milk and flour as the main component. This study aims to determine the organoleptic characteristics including overall acceptance and texture quality and aroma quality in cubit tempe cakes, to determine the best antioxidant activity against tempe pinch cakes, and calculate the nutrient content produced in 1 portion of the best cubit tempe cakes. This study uses an experimental method with the type of Randomized Block Design. There are 5 treatments with the ratio of 80 g flour, 75 g, 70 g, 65 g, 60 g and tempe 20 g, 25 g, 30 g, 35 g, 40 g. The result of variance on cubit cake smell, taste, texture, colour, acceptance tempe as a whole, the quality of the smell, the quality of the texture obtained the quality of the results were not significantly different. Cubit cake with the best characteristics, namely the ratio of 60 grams of wheat flour and 40 grams of tempe with the overall acceptance characteristics preferred, chewy texture and unpleasant smell and nutrients in one recipe that is ash content of 2.46 grams, water content of 155.73 grams, protein 23.12 grams, fat 13.02 grams, carbohydrates 75.17 grams.